The Effectiveness of Using the HelloTalk Application in Improving English Speaking Fluency: An Experimental Approach at SMAN 1 Pamona Utara - Binti, Viel Chensist; Mukrim, Mukrim; Maghfira, Maghfira; Usman, Sriati (Journal of English Language and Education, 2025)
Eglish is an international language widely used in education, work, and intercultural communication. Speaking fluency is a crucial component of speaking skills because it enables learners to convey ideas smoothly and spontaneously. This study aimed to examine the effectiveness of using the HelloTalk application in improving students’ English speaking fluency. A quasi-experimental design was employed involving two classes: an experimental group taught using HelloTalk and a control group taught using conventional methods. The data were collected through pre-test and post-test speaking assessments and analyzed using an independent sample t-test. The findings revealed that the mean post-test score of the experimental group (68.5) was higher than that of the control group (62.25), with t-count (5.85) exceeding t-table (2.002), indicating a significant difference. These results suggest that HelloTalk is effective as a learning medium for improving students’ English speaking fluency through interactive and authentic communication.